BUSINESS GROWTH IN NASARAWA STATE: EFFECT OF MULTIPLE TAXATION - Okon, Emmanuel O.; Agbaji, Joseph S.; Alabi, John O. (International Journal For Research In Business, Management And Accounting, 2016)
The study assesses the effect of multiple taxation on business growth in Nasarawa state, Nigeria. A survey research method was adopted. A sample of 420 business owners/operators were randomly selected from some selected towns in Nasarawa state. Questionnaire was the major instrument used for data collection. Tables, graphs, percentage and other simple statistical tools were used in the analysis of the data collated. A total of 53.81% of the respondents were of the view that multiple taxes affect their businesses significantly/very significantly. This was confirmed by the Z – Test statistical tool was used to test the formulated hypotheses. Therefore, it is recommended that the list of approved or authorized taxes and governments agents should be harmonized and published. In addition, unauthorized revenue agencies should be reported to relevant government agencies for sanction.